PEDAGOGICAL VIEWS OF JADID ENLIGHTENERS - Hasanova , Sevinch; Islomova , Komila (Journal of Pedagogical and Philological Research, 2026)
This article provides a profound analysis of the pedagogical activities of Turkestan Jadid enlighteners and the significance of enlightenment movements in developing today’s education system. It also explores the Jadids’ views on national ideology and concepts. Furthermore, the article comprehensively analyzes the pedagogical activities of Turkestan enlighteners and their profound impact on the modern educational framework. In our research, we utilized a methodological approach and made extensive use of primary sources. Therefore, the primary objective of this study is to research the activities of enlightenment, which is considered a vital and fundamental part of the Jadidism movement.Based on the materials studied during the research process, the scientific basis for how the actions of Turkestan Jadids in the field of pedagogy—specifically their advanced ideas on teaching subjects and delivering knowledge to students—align with the methodology of various subjects was established.